Corrections to “Enhancing Detection of Control State for High-Speed Asynchronous SSVEP-BCIs Using Frequency-Specific Framework” - Yufeng Ke; Jiale Du; Shuang Liu; Dong Ming (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
In the above article [1], we found the formula (1) is presented incorrectly because of an error in the formula editing process. The correction is as follows: